Smart Railway Station Energy Management Considering Regenerative Braking and ESS - Sengor, Ibrahim; Kilickiran, Hasan Can; Akdemir, Huseyin; Kekezoglu, Bedri; Erdinc, Ozan; Catalao, Joao P. S. (IEEE, 2017)
Optimum operation of the energy consumption of end-users gains more importance to reduce total electricity bills and in order to more efficiently use energy resources thanks to smart grid concept. Electrical railway stations are one of the best places to take into account for in this manner. This study proposes a railway station energy management (RSEM) model. As the main contribution to the literature, regenerative braking energy (RBE) recovered during the operation of a metro line is assumed to meet the station load demand in daily operation. The RSEM model composed of RBE usage, energy storage system (ESS), and grid support is formulated as a mixed-integer linear programming (MILP) framework. RSEM model is tested by introducing the impact of passengers change on RBE for such cases that whether RBE and ESS are considered or neglected.
Keywords: Energy storage; mixed integer linear programming; railway energy management; regenerative breaking energy; Computer Science; Engineering